A teoria de Kohlberg sobre o desenvolvimento do raciocínio moral e os instrumentos de avaliação de juízo e competência moral em uso no Brasil - Bataglia, Patrícia Unger Raphael [UNESP]; Morais, Alessandra de [UNESP]; Lepre, Rita Melissa [UNESP] (PPgPsi-UFRN, 2010)
O presente artigo tem por objetivo abordar as bases, finalidades e composição de dois instrumentos de avaliação de juízo moral: a Moral Judgment Interview (MJI) e o Defining Issues Test (DIT), e um de competência moral: o Moral Judgment Test (MJT). Retoma a teoria do desenvolvimento moral de Kohlberg que fundamenta esses instrumentos, assim como os últimos estudos realizados com os mesmos. A MJI é uma entrevista semiestruturada que avalia o nível de juízo moral. O DIT é um teste objetivo que mede a proporção de respostas pós-convencionais. O MJT é um instrumento objetivo, que avalia a competência moral. Destaca-se a crescente utilização desses instrumentos em pesquisas sobre moralidade.

This paper presents intends to address the objectives and composition of two instruments for evaluation of moral judgment: the Moral Judgment Interview (MJI) and the Defining Issues Test (DIT) and one for moral competence measurement: the Moral Judgment Test (MJT). It retakes Kohlberg's moral development theory which gives the foundation for these instruments. Presents Brazilian studies with each instrument. MJI is a semi-structured interview that evaluates the stage of moral judgment. DIT is an objective test that measures the percentage of post-conventional answers. MJT is an objective instrument that measures the moral judgment competence. Researches have used more and more these instruments.
Kohlberg's theory about moral judgment development and the instruments used for evaluation of moral judgment and moral competence in Brazil
Keywords: instrumentos de avaliação; juízo moral; competência moral; instruments for measurement; moral judgment; moral competence